Key environmental factors to variation of ammonia-oxidizing archaea community and potential ammonia oxidation rate during agricultural waste composting. (December 2018) - Ren, Liheng; Cai, Changqing; Zhang, Jiachao; Yang, Yuan; Wu, Genyi; Luo, Lin; Huang, Hongli; Zhou, Yaoyu; Qin, Pufeng; Yu, Man
Graphical abstract: Highlights: Key factors for AOA community and PAO rate during composting were determined. AOA were abundant and 22 gene OTUs divided into the soil/sediment lineage. AOA structure significantly explained by OM, pH and nitrate (85.6%, P = 0.002). AOA amoA gene structure was significantly explained by TOC, pH and nitrate. PAO rate correlated positively to ammonium, AOA amoA gene abundance. Abstract: In this research, the abundance and structure of AOA amoA gene during agricultural waste composting were determined by quantitative PCR and sequencing techniques, respectively. Pairwise correlations between potential ammonia oxidation (PAO) rate, physicochemical parameters and the AOA abundance were evaluated using Pearson correlation coefficient. Relationships between these parameters, PAO rates and AOA community structure were evaluated by redundancy analysis. Results showed that 22 AOA gene OTUs were divided into the soil/sediment lineage by phylogenetic analyses. Significant positive correlations were obtained between AOA amoA gene abundance and moisture, ammonium, water soluble carbon (WSC) and organic matter (OM), respectively. Redundancy analysis showed OM, pH and nitrate significantly explained the AOA amoA gene structure. Pearson correlation revealed the PAO rate correlated positively to ammonium, AOA amoA gene abundance. These results indicated that AOA communities sense the fluctuations in surrounding environment, and ultimately react and influence the nitrogen transformation during agricultural waste composting.